1998
DOI: 10.1021/ic9809299
|View full text |Cite
|
Sign up to set email alerts
|

The Solution Structure of a Copper(II) Compound of a New Cyclic Octapeptide by EPR Spectroscopy and Force Field Calculations

Abstract: A new cyclic octapeptide, cyclo(Ile-Ser-(Gly)Thz-Ile-Thr-(Gly)Thz) (PatN), related to patellamide A, has been synthesized and reacted with copper(II) and base to form mono- and dinuclear complexes. The coordination environments around copper(II) have been characterized by EPR spectroscopy. The solution structure of the thermodynamically most stable product, a purple dicopper(II) compound, has been examined by simulating weakly dipole-dipole coupled EPR spectra based upon structural parameters obtained from for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 42 publications
1
60
1
Order By: Relevance
“…The observation that, despite the biotoxicity of Cu II , its concentration in the ascidians is roughly 10 4 times higher than in the surrounding sea water, has fostered the interest in the macromolecule's metal ion, and especially Cu II coordination chemistry. 34,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] The focus of this perspective is on the Cu II coordination chemistry of the L. patella and L. bistratum cyclic peptides and a series of synthetic analogues. Structure and dynamics of the metal-free ligands and their applications are also reviewed.…”
Section: Nina Dovalilmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that, despite the biotoxicity of Cu II , its concentration in the ascidians is roughly 10 4 times higher than in the surrounding sea water, has fostered the interest in the macromolecule's metal ion, and especially Cu II coordination chemistry. 34,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] The focus of this perspective is on the Cu II coordination chemistry of the L. patella and L. bistratum cyclic peptides and a series of synthetic analogues. Structure and dynamics of the metal-free ligands and their applications are also reviewed.…”
Section: Nina Dovalilmentioning
confidence: 99%
“…124 The binding constants for a series of cyclic peptides from L. patella and L. bistratum together with synthetic analogues are assembled in Table 1 , Scheme 2; the heterocycles of these ligands were not closed so far although this should be feasible). 48,53 These syntheses were quite tedious and did not yield sufficient quantities of the ligands for comprehensive studies of the solution coordination chemistry. However, based on ESI-MS, electronic (UV-vis-NIR and CD) and EPR spectroscopy, we have been able to fully characterize the main mono-and dinuclear species in solution.…”
Section: Lissoclinum Bistratum Derived Peptidesmentioning
confidence: 99%
“…Therefore, a small value of A k is expected. [8,[44][45][46][47] IR spectroscopy: Upon coordination of H 3 L 1 to copper(II), there is a shift of the CO peptide vibrational band in the IR spectrum from 1656 cm À1 in the metal-free macrocycle to 1617 cm À1 in the copper(II) complex. Such a shift would be expected for the substitution of hydrogen of a peptide group by a metal ion.…”
Section: J Can Contribute To the Zero-field Splitting (S·j·s) If The mentioning
confidence: 99%
“…The basic structure of patellamides consists of a cyclic octapeptide containing two thiazole and two oxazoline rings (Scheme 1). The structure binds two metal atoms, typically copper atoms although studies of other bound metals have been reported as well [36][37][38][39][40]. The patellamides are split into two classes, symmetric and asymmetric, distinguished from each other by the absence or presence of a phenylalanine residue, respectively.…”
Section: Introductionmentioning
confidence: 99%